2006
DOI: 10.1029/2005jd005941
|View full text |Cite
|
Sign up to set email alerts
|

North African soil dust and European pollution transport to America during the warm season: Hidden links shown by a passive tracer simulation

Abstract: A mesoscale atmospheric model coupled with a dispersion model is used to establish source‐receptor relationships between the European‐North African aerosol episodes observed over the Caribbean every year during summer and their main sources. The simulation period extends from 15 July to 16 August 1991, concurrent with the flight campaign of the European Project RECAPMA (Millán et al., 1997; Gangoiti et al., 2001). We now extend the simulations to reach the tropical Atlantic and the Caribbean, and we make use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…6b): air originally from the Mediterranean flows north to south across Tunisia and Northern Algeria and is then westward transported along the southern slope of the Atlas mountains toward the North Atlantic Ocean. This transport pathway is similar to the "mean airflows" previously described by Millán et al (1997) and Gangoiti et al (2006). This transport pathway is the result of the meteorological scenario typical of the summertime (Fig.…”
Section: Transport Pathways Of Saharan Airflowsmentioning
confidence: 49%
See 2 more Smart Citations
“…6b): air originally from the Mediterranean flows north to south across Tunisia and Northern Algeria and is then westward transported along the southern slope of the Atlas mountains toward the North Atlantic Ocean. This transport pathway is similar to the "mean airflows" previously described by Millán et al (1997) and Gangoiti et al (2006). This transport pathway is the result of the meteorological scenario typical of the summertime (Fig.…”
Section: Transport Pathways Of Saharan Airflowsmentioning
confidence: 49%
“…Studies performed by Millán et al (1997) and Gangoiti et al (2006) have shown that aged pollutants emitted in Eastern Spain and re-circulated in the Western Mediterranean basin may also be mixed with North African desert dust, and then be exported to the North Atlantic in the SAL. These coastal and mountain breezes involved in the regional transport and aging of pollutants have also been described for the North African side of the Western Mediterranean (Algeria -Tunisia; Bouchlaghem et al, …”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dust is frequently mixed with particulate pollutants in the Saharan Air Layer (Rodríguez et al, 2011). In addition to sources related to industrial and local population centres on the African continent, pollutants from Europe and North America can be rapidly transported to Africa where they are mixed with dust-laden air masses (Astitha et al, 2010;Fomba et al, 2013;Gangoiti et al, 2006;Kallos et al, 1998). Koçak et al (2005) observed higher levels of excess Pb in dust-rich air from Africa than in air from other sectors, which they suggested may be due to Saharan dust acting as an impaction or adsorption surface for finer anthropogenic aerosols, although they could not rule out the possibility of higher anthropogenic emissions from Africa being partly or wholly responsible for the observation.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Several studies have shown that mineral dust in the atmosphere is often mixed with anthropogenic aerosol (e.g. Kandler et al, 2007;Gangoiti et al, 2006). Recently, Rodríguez et al (2011) showed that anthropogenic emissions from crude oil refineries and power plants, located on Northern African coasts, contribute to desert dust mixing with particulate pollutants.…”
Section: Introductionmentioning
confidence: 99%